Creep behavior of RC slabs strengthened NSM CFRP laminate strips under different environmental conditions - Sena-Cruz, José (2013)
With the aim of analyzing the long-term deformational performance of concrete elements flexurally strengthened with the near-surface mounted (NSM) technique, an experimental program has been launched using slab specimens submitted to sustained loads under the following environmental conditions: (i) 20ºC temperature and 55% relative humidity; (ii) immersed in water tank at 20ºC with 0% of chlorides; (iii) immersed in water tank at 20ºC with 2.5% of chlorides; (iv) submitted to wet/dry cycles at 20ºC with 2.5% of chlorides. The slabs are continuously monitored in terms of mid-span vertical deflection and strains (in concrete, CFRP laminate strip and steel reinforcements). The present paper summarizes the preliminary results obtained in this ongoing project.